الصناعات الصوفية التقليدية والتنمية المحلية في جبل نفوسة - أ. عزالدين عبدالله المقدمي (Sharwes Scientific Journal, 2025)
This research aims to introduce the traditional wool industries in the Nafusa Mountains, as they have been and continue to be significant sectors due to their cultural, social, and economic dimensions. These industries have contributed effectively to local development, preservation of cultural heritage, and the national identity, especially during religious and social occasions. The research aims, through statistical analysis, to highlight the challenges facing this industry and to work on finding scientific solutions for the development of traditional wool industries specifically in the Nafusa Mountains, which is the focus of this study, and in Libya more broadly. This is achieved through a questionnaire distributed to a random sample of 91 artisans from three age groups: under 30 years, from 30 to 50 years, and over 50 years. The overall results of the statistical analysis of the variables indicate that the calculated t value for most variables and their total score is greater than the tabulated value of (1.66), and the level of significance is less than (0.05). This results in generalizing the findings obtained from the sample to the research community. Additionally, it was found that more than 95% of the sample responded to the questionnaire, indicating that the results are very close to reality.